Architecture of Legal Reasoning - Manzin, Maurizio (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
In the first part of my article I outline some basic concepts about the relation between architecture and law in the domain of L&L studies, as well as the one of “visual” metaphor recently worked out by some argumentative scholars. Then I discuss the architectural forms of some buildings (the Greek temple, the early medieval church, the gothic cathedral, the skyscraper, the postmodern building) which have been chosen on the basis of their representativeness regarding the respective ages: my aim is to stress the parallel between each of them and the contemporary kind of legal reasoning. In conclusion, I propose to interpret the modern era as a constant attempt to eliminate thaumazein in favor of certainty-predictability. Parole chiave: Architecture and Law; Visual metaphor; Postmodernity; Legal reasoning; Thaumazein Indice: 1. Premessa – 2. L’analogia fra architettura e diritto – 3. Metafore “visuali” – 4. Prima forma: il tempio greco – 5. Seconda forma: la chiesa preromanica – 6. Terza forma: la cattedrale gotica – 7. Quarta forma: il grattacielo – 8. Quinta forma: l’edificio free hand – 9. “Conti” e “racconti”: chi ha paura del Vecchio Uomo Salice? – Riferimenti bibliografici